(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we are presenting the Estimation of space in Hyderabad using Neuro Fuzzy approach in Digital image processing. Digital image processing is the science of manipulation of an image by means of a processor. The advantage of combining neural networks with fuzzy logic is that, it is better in noisy environment as picture not to do and it has fault tolerance capability better than individual approach, so we are working for a better result using this approach in image processing. Every intelligent technique has particular computational properties (e.g. ability to learn, explanation of decisions) that make them suited for particular problems and not for others. For example, while neural networks are good at recognizing patterns, they are not good at explaining how they reach their decisions. Fuzzy logic systems, which can reason with imprecise information, are good at explaining their decisions but they cannot automatically acquire the rules they use to make those decisions. Hybrid systems are also important when considering the varied nature of application domains. Many complex domains have many different component problems, each of which may require different types of processing. Fuzzy logic provides an inference mechanism under cognitive uncertainty,computational neural networks offer exciting advantages, such as learning, adaptation, fault-tolerance, parallelism and generalization.